Artificial Intelligence (AI)-Based Public Policy: Challenges and Opportunities for State Administration in the Society 5.0 Era - Wirawan Zaenal; Astuti Astuti (Eduvest - Journal of Universal Studies, 2025)
The development of Artificial Intelligence (AI) has brought significant changes to public administration and public policy in the era of Society 5.0. This study analyzes the opportunities and challenges of implementing AI in government using a qualitative approach through literature review and policy analysis. The study finds that AI has the potential to improve the efficiency of public services through automation, policy data analysis, and intelligent government systems. However, there are complex challenges to its adoption, such as regulatory gaps, data privacy concerns, bureaucratic resistance, and the digital divide. Key findings from this study identify three critical issues: (1) the urgency of AI ethics and data protection accountability, (2) a phased approach that prioritizes specific sectors (health, education), and (3) public education to build understanding and trust. This study also highlights the potential of AI to improve government accountability through fraud detection and public-private partnerships. This study advocates a human-centered AI governance model that balances technological innovation with public transparency, citizen engagement, and principles of social justice.